JSE 32:1 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2018)
With the recent passing of SSE co-founder, Robert Jahn, our Society has suffered a great loss. So in this issue we pay tribute to Bob and honor his considerable achievements both within and outside mainstream science. The eloquent testimonials in this issue make it clear just how central Bob has been to the intellectual and administrative life of the SSE, and also how extensive and varied his scientific contributions have been. For relative newcomers to the SSE and JSE, perhaps unfamiliar with Bob’s work, I enthusiastically recommend perusing (for free, of course) back issues of the JSE for the many papers that bear his name. It’s an unusually impressive body of work, and only a small portion of his intellectual legacy. To facilitate my recommended literature search, here’s a list of all of Bob’s JSE papers, followed by a selection of his other publications.